Effect of Kind and Dosage of Enrichment Materials on the Nutritional Quality of Rotifers Especially n3-HUFA - Suprayudi, Muhammad Agus (Indonesian Society of Scientific Aquaculture (ISSA), 2003)
This experiment was conducted to evaluate the quality of rotifer enriched with four kinds of enrichement materials from the stand point of essensial fatty acids. Rotifer was enriched at 24 - 25oC for 18 hours at a density of 1000 ind/ml. Rotifers were treated by four kinds of enrichment materials such as oleic acid (R-OA), two different density of Nannochloropsis oculata, (4x107 and 16x107 cell/ml; R-N18 and R-N42) two different levels of eicosapentaenoic acids (EPA) triglyceride type (EPA-TAG) (20 and 40 ml/ml; R-E20, R-E40) and two different level of EPA ethyl ester (EPA-EE) (R-EE25 and R-EE50%) respectively. Rotifers enriched with Nannochloropsis oculata and EPA-EE type have a similar profile of essensial fatty acid especially on n3-HUFA that dominated by EPA, while DHA was in a trace amount or not detected. In addition Nannochloropsis oculata as an enrichment material showed the highest population density of rotifers during enrichment periods. Rotifer enriched with EPA-TAG has a more complete of essential fatty acid profile compared to other enrichment materials due to their contained both of EPA and DHA. We conclude that rotifer enriched with EPA-TAG as enrichment material showed the best nutritional quality of rotifers from the stand point of essential fatty acid. Key words : Rotifers, enrichment, eicosapentaenoic acid, docosaheksaenoic acid, n3-HUFA ABSTRAK Penelitian ini dilakukan untuk mengetahui profil asam lemak rotifera yang diperkaya dengan berbagai macam jenis dan dosis pengkaya. Rotifera dengan kepadatan 1000 ind./ml diperkaya dengan bebagai bahan pengkaya seperti asam oleat (R-OA); Nannochloropsis oculata dengan kepadatan 4x107 dan 16x107 sel/ml (R-N18 dan R-N42); eicosapentaenoic acid (EPA) tipe triglicerida (EPA-TAG) dengan dosis 20 dan 40 μl (R-E20 dan R-E40) dan EPA tipe ethyl esther (EPA-EE) dengan dosis 25 dan 50 μl per liter (R-EE25 and R-EE50%). Rotifera diperkaya selama 18 jam pada suhu 24-25oC. Rotifera yang diperkaya dengan Nannochloropsis oculata serta EPA-EE memiliki kesamaan profil asam lemak terutama pada incorporasi EPA, sedangkan DHA terkandung pada jumlah yang kecil atau tidak terdeteksi. Adapun rotifera yang diperkaya dengan EPA-TAG memiliki profil asam lemak yang lebih lengkap terutama ditinjau dari kandunga EPA dan docosahexaenoic acid (DHA) nya. Selanjutnya rotifera yang diperkaya dengan Nannochloropsis oculata memiliki populasi yang tertinggi dibanding perlakuan lainnya. Dari penelitian ini dapat disimpulkan bahwa pengkayaan dengan EPA-TAG memiliki kualitas rotifera yang terbaik ditinjau dari sisi kelengkapan kandungan asam lemaknya. Kata kunci : Kualitas rotifera, pengkayaan, asam eikosapentaenoik, asam dokosaheksaenoik, n3-HUFA